Enriching short stories through processes – A functional approach. (June 2016) - Lee, Jackie F.K.
Abstract: The present study aims to use a genre-based functional grammar approach to examine how grammar instruction can help improve Hong Kong English learners' story writing performance. Four classes of Secondary 1 (Grade 7) students participated in the study, with one class being the control group. The experimental groups received instructions in a research lesson that highlighted the impact of their choice of process types on story writing, while the control group did not receive any functional grammar instruction. A comparison of the writing performance of the experimental groups in the pre- and post-lesson tests revealed significant improvement, while no progress was found with the control group. The test results were triangulated with the students' class writing and homework, and nine selected students' pre- and post-lesson interview data. The findings revealed students' heightened awareness of the impact of the choice of various processes on writing. The study also found that lower achievers gained substantial benefits from the explicit writing instruction. This study provides insights to ESL/EFL teachers about how to use functional grammar as a pedagogical tool to enhance learners' story writing skills.